OP0107 Adipocytokines imbalance is associated with vascular damage in systemic sclerosis. (12th June 2018) - Bosello, S.; De Lorenzis, E.; Canestrari, G.; Natalello, G.; Di Mario, C.; Gigante, L.; Barini, A.; Barini, A.; Verardi, L.; Tolusso, B.; Ferraccioli, G.; Gremese, E.
Abstract : Background: Adipocytokines are implicated in the development of fibrosis, vasculopathy and immune abnormalities through a variety of biological effects, but their role in systemic sclerosis (SSc) is not fully investigated. Chemerin is implicated in chemotaxis of immune cells, in promoting angiogenesis and it is involved in inflammation. Adiponectin (APN) has metabolic actions and anti-inflammatory properties, while Leptin (LEP) mediates actions in endothelial cells, such as angiogenesis, vasodilation, NO production and upregulates various mediators of vascular inflammation. Objectives: In this study we investigated Chemerin, LEP and APN levels in SSc patients according to disease subtypes and clinical characteristics. Methods: Chemerin, LEP and APN levels were evaluated in 100 SSc patients and in sex, age and BMI matched healthy controls. Clinical and demographical characteristics were available for all patients. Results: Chemerin, APN and LEP levels were lower in SSc patients compared to healthy controls (Chemerin: 58.7±27.6 ng/ml vs 74.0±29.0 ng/ml, p=0.004; LEP:19.6±18.3 ng/ml vs 28.5±23.8 ng/ml, p=0.03, APN: 6.5±3.9 µg/ml vs 12.8±6.0 µg/ml, p<0.001) Chemerin levels were lower in patients with anti-topoisomerase antibodies (50.2±22.7 ng/ml) respect to patients with other autoantibodies (64.6±29.7 ng/ml), p=0.018. Regarding capillaroscopic damage, Chemerin levels were lower in patients with late pattern (44.8±18.9 ng/ml) compared to patients with early (64.3±28.5 ng/ml) and active pattern (71.7±29.9 ng/ml), p<0.001. APN levels inversely correlate with IL-6 levels (R=-0.4, p<0.001), while directly correlate with capillary density (R=0.3, p=0.03). Patients with avascular areas presented lower levels of APN (5.3±3.9 µg/ml) compared to patients without avascular areas (7.3±3.4 µg/ml), p=0.005. LEP levels directly correlate with vascular density on nailfold capillaroscopy (R=0.3, p=0.02), confirming the role of LEP in endothelial homeostasis. Furthermore, patients with avascular areas presented lower LEP levels (15.5±13.0 ng/ml) compared to patients without avascular areas (31.1±28.4 ng/ml), p=0.003. LEP levels were lower in patients with active digital ulcers (9.3±6.6 ng/ml), compared to patients without ulcers (9.3±6.6 ng/ml), p=0.01. The anti-inflammatory and endothelium protective role of APN emerged also when we considered the lung involvement: in fact patients with DLCO >50% presented higher levels of APN (7.0±3.9 µg/ml) compared to patients with DLCO <50% (5.8±3.8 µg/ml), p=0.05. Considering the cardiopulmonary involvement, LEP levels inversely correlate with PAPs on echocardiography (R=-0.24, p=0.02). Finally LEP levels inversely correlate with skin score (R=-0.3, p=0.009) and patients with early disease presented lower LEP levels (15.1±13.2 ng/ml) compared to patients with long lasting disease (29.9±28.7 ng/ml), p=0.006. Conclusions: Our data suggest an imbalance of the levels of adipocytokines in SSc, their down-regulation in patients with a more aggressive pattern on nailfold videocapillaroscopy and organ damage, suggesting a possible role of Chemerin, LEP and APN in the impaired angiogenesis and in the development of vasculopathy of SSc patients. Disclosure of Interest: None declared